Effect of Saline Water Irrigation on Sodium and Potassium Uptake in Up 301 Wheat (Triticum Aestivum L.) - Murthy, A S P; Ramu, M N Venkata; Yadav, J S P (Annals of Arid Zone, 2016)
The results of the effect of varying salinity levels of irrigation water on the yield and mineral content of UP 301 wheat (Triticum a.estivum L.) under field conditions are reported. Mineral analysis of the leaf tissue reflected the effect of the saline water. Grain yield of wheat decreased progressively with an increase in Na and/or decrease in K concentration in the leaf. Sodium level of 23.49 mcq/l00g in the leaf extract reduced the grain yield by about 61 percent of the control, while a 50 percent decrement in grain yield was associated with 19.2 meq/1OO g of Na and K/Na ratio of 5 in the leaf. The data suggest that the K/Na and K/Ca ratios are positively related to salt tolerance of UP 301 wheat as shown by linear correlation studies.